2018
DOI: 10.1177/0022487118788838
|View full text |Cite
|
Sign up to set email alerts
|

An Affinity for Learning: Teacher Identity and Powerful Professional Development

Abstract: Drawing on interviews with a diverse sample of teachers, this study uses the frame of professional identity to interpret the heterogeneity among teachers’ perceptions of professional development. Specifically, it examines how teachers’ “anchoring beliefs” might be reflected in or refracted by their accounts of powerful professional learning. An analysis of three case studies of teacher identity and teacher learning reveals three distinct “learning affinities”: for the what (content), the who (facilitation), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 36 publications
1
59
0
2
Order By: Relevance
“…Although personal identity and professional identity work in conjunction with one another, they are still developed through separate experiences and later used to inform decisions and actions. In 18 of 23 cases in his study, James Noonan (2018) found that there was an "alignment between participants'…”
Section: Personal Vs Professionalmentioning
confidence: 96%
See 2 more Smart Citations
“…Although personal identity and professional identity work in conjunction with one another, they are still developed through separate experiences and later used to inform decisions and actions. In 18 of 23 cases in his study, James Noonan (2018) found that there was an "alignment between participants'…”
Section: Personal Vs Professionalmentioning
confidence: 96%
“…A teacher's PI is constantly evolving, contingent upon a variety of factors, including experiences, the environment, interactions with people, and the context of a given scenario (Noonan, 2018). Through different contexts, teachers develop their PI (Ruohotie-Lyhty & Moate, 2016), which can have an impact on different aspects of their career, such as instruction, interactions with students, and teaching philosophy.…”
Section: Professional Identity Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also necessary to bear in mind the stress-triggering nature of the lockdown, during which the teaching staff had to cope with arising difficulties and to adapt to the new reality very quickly. Besides, the teachers found themselves excluded from the professional community that had previously facilitated their professional self-fulfilment (Noonan, 2018;Prenger et al, 2018). The competencies of working with a particular online tool is formed relatively quickly; however, the difficulties related to the low level of the psychological and teaching readiness of the staff are harder to cope with, and they often become a serious barrier for remote learning of high quality.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign colleagues discussing the professional development, professional identification, emphasize the importance of the professional community (Blackmore, Howard & Kington 2018;Noonan,. 2018;Prenger, Poortman, & Handelzalts, 2018;Cherng & Davis 2017).…”
Section: Introductionmentioning
confidence: 99%